PENGARUH TARIF PAJAK, SANKSI PAJAK, PENEGAKAN HUKUM, KEADILAN SISTEM PAJAK DAN TRANSPARANSI ALOKASI DANA PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA SEMARANG - Adelia Putri Qani’ah Soeyanto; Wahyu Meiranto (Diponegoro Journal of Accounting, 2025)
This study aims to evaluate the effect of tax rates, tax sanctions, law enforcement, tax system fairness, and transparency of tax fund allocation on taxpayer compliance in Semarang City. This study uses the Theory of Planned Behavior (TPB) framework developed by Ajzen (2005) which explains that a person's behavior is determined by intention.This study uses a quantitative approach with a survey method, data collected through questionnaires distributed to 212 respondents who are individual taxpayers. The data obtained was then analyzed with the Partial Least Squares Structural Equation Modeling (PLS-SEM) model using the SmartPLS version 4 application. The results of the analysis show that tax rates have no significant effect on taxpayer compliance, while tax sanctions are proven to have a positive and significant effect. Law enforcement and tax justice showed no significant effect on compliance, while transparency of tax fund allocation had a positive and significant effect. These findings emphasize the importance of increasing taxpayer trust in tax authorities to improve taxpayer compliance.